Role of laparoscopy in blunt abdominal trauma (Journal of Pharmaceutical Negative Results, 2022)
Blunt trauma account around 95% of injuries. Approximately 15% of the overall trauma injuries affect the abdomen and considered a leading cause of death in young adults. Although Laparotomy is considered as a standard procedure for managing traumatized cases, laparoscopic techniques increasingly used as an alternative procedure. The aim of the current study is to assess the effectiveness of laparoscopy in managing patients with blunt abdominal trauma to avoid unnecessary laparotomies. The study was conducted as prospective cohort study on 32 patients with isolated blunt abdominal trauma (15 (46.8%) patient with motor vehicle collision; 5 (15.6%) fall from height; 3 (9.37%) assault; and 9 (28.12%) automobile pedestrian accident) who attend causality unit at Al jumhory Hospital from 1/2/2020 to 1/8/2022. The age ranged from 12 to 60 years, composed of 29 males and 3 females. Laparoscopic inspection of peritoneal cavity revealed the following: splenic injury in 17 patients (53.12%); liver injury (Grade-I,II, and III) in 5 (15.6%) patients; omental bleeding in 2 (6.25%); mesenteric bleeding and hematoma in 6 (18.75%); and Jejunal injuries in 2 (6.25%) patients The mean operative time was 123.28 min and the postoperative ICU stay 1.5 days. Various complications were reported in 7 (21.87%) of patients. In conclusion, laparoscopy is considered as effective procedure in managing patient sustained blunt abdominal trauma that reduce the rate of laparotomy with lower morbidity and mortality rates.